2014
DOI: 10.1007/s10802-013-9841-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Bullying and Victimization: Student- and Classroom-Level Mechanisms of Change

Abstract: This longitudinal study examines the mediating mechanisms by which the KiVa antibullying program, based on the Participant Role approach, reduces bullying and victimization among elementary school students. Both student-level mechanisms leading to reduced perpetration of bullying and classroom-level mechanisms leading to reductions in bullying and victimization are considered. Analyses are based on a sample of 7,491 students (49.5% boys) nested within 421 classrooms within 77 schools. At the beginning of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
128
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 34 publications
9
128
0
5
Order By: Relevance
“…the proportion of boys in a classroom, the proportion of immigrants in a classroom), or the findings have been controversial. Classroom differences can be better explained by factors related to peer group dynamics or teacher characteristics (for a review, see Saarento, Boulton, & Salmivalli, 2015).…”
Section: Classroom-level Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…the proportion of boys in a classroom, the proportion of immigrants in a classroom), or the findings have been controversial. Classroom differences can be better explained by factors related to peer group dynamics or teacher characteristics (for a review, see Saarento, Boulton, & Salmivalli, 2015).…”
Section: Classroom-level Risk Factorsmentioning
confidence: 99%
“…A study examining the mediators of the KiVa antibullying programme (Saarento et al, 2015) found that changes in student perceptions of their teachers' bullying-related attitudes mediated the effects of the programme on bullying. During the year when the KiVa programme was implemented, students started to perceive their teachers' attitudes as more disapproving of bullying, and consequently, their bullying behaviour was reduced.…”
Section: Classroom-level Risk Factorsmentioning
confidence: 99%
“…Group-based interventions, including KiVa, emphasize that bullying is a group phenomenon; the aim is to increase empathy for victims, and develop bystanders' efficacy to counteract bullying in safe ways, so that more students disapprove of bullying and stand up for victims (Saarento et al 2014). However, targeting peer dynamics still implies that victimized children possess qualities that make them desirable as friends.…”
Section: Obstacles To Intervention Effectsmentioning
confidence: 99%
“…Research has mostly studied bullying at the peer group level, emphasizing its role in influencing the current and future behaviors of the perpetrators, victims, and witnesses (Salmivalli et al, 1996;Salmivalli, 2010;Boulton et al, 2017). However, while reactions from peers certainly affect how students may become involved in and cope with these events (Saarento et al, 2015), other facts are just as important.Recent research has stressed the role of teachers in recognizing episodes of bullying and identifying their actors, as well as in preventing and intervening on them (DeOrnellas and Spurgin, 2017 reinforces or inhibits the various possible behaviors on the part of the bullies, the victims, and the bystanders (Craig et al, 2011), and in general affects how pupils perceive and react to bullying (Gini, 2005;Twemlow et al, 2006;Bjereld et al, 2017). Indeed, there is evidence showing that students who perceive their teachers as disapproving of bullying are less likely to bully others; conversely, bullying is more common when students feel that their teachers tolerate it (Saarento et al, 2013).…”
mentioning
confidence: 99%
“…Research has mostly studied bullying at the peer group level, emphasizing its role in influencing the current and future behaviors of the perpetrators, victims, and witnesses (Salmivalli et al, 1996;Salmivalli, 2010;Boulton et al, 2017). However, while reactions from peers certainly affect how students may become involved in and cope with these events (Saarento et al, 2015), other facts are just as important.…”
mentioning
confidence: 99%